2012
DOI: 10.5402/2012/375231
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Calcitonin Levels and [F18]FDG-PET/CT in the Detection of Recurrence in Patients with Sporadic and Hereditary Medullary Thyroid Cancer

Abstract: Purpose. Measurement of serum calcitonin is important in the followup of patients with medullary thyroid carcinoma (MTC) and reliably reflects the presence of the disease. This is the largest study so far in bibliography investigating the diagnostic accuracy of combined [18F]FDG-PET/CT in patients with MTC and elevated calcitonin levels. Methods. Between February 2007 and February 2011, 59 [18F]FDG-PET/CT were performed on 51 patients with MTC and elevated calcitonin levels for localization of recurrent diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Even a low positive detection rate of 18 F-FDG-PET in such patients will affect the management of a significant number of patients. In line with this, Skoura et al [5] reported an overall per-patient sensitivity of 44.1 % in 51 MTC patients with increased Ct The meta-analysis by Treglia et al [4] reported increased detection rates of 18 F-FDG-PET/(CT) of 69 % if CEA was [5 ng/mL, 75 % if Ct was [1,000 ng/L, 76 % if Ct Dt was \12 months and as high as 91 % if CEA Dt was \24 months. In line with this, we observed a strong correlation between elevated tumor marker concentrations and 18 F-FDG PET/CT SUV max [6].…”
supporting
confidence: 66%
See 3 more Smart Citations
“…Even a low positive detection rate of 18 F-FDG-PET in such patients will affect the management of a significant number of patients. In line with this, Skoura et al [5] reported an overall per-patient sensitivity of 44.1 % in 51 MTC patients with increased Ct The meta-analysis by Treglia et al [4] reported increased detection rates of 18 F-FDG-PET/(CT) of 69 % if CEA was [5 ng/mL, 75 % if Ct was [1,000 ng/L, 76 % if Ct Dt was \12 months and as high as 91 % if CEA Dt was \24 months. In line with this, we observed a strong correlation between elevated tumor marker concentrations and 18 F-FDG PET/CT SUV max [6].…”
supporting
confidence: 66%
“…Even a low positive detection rate of 18 F-FDG-PET in such patients will affect the management of a significant number of patients. In line with this, Skoura et al [5] reported an overall per-patient sensitivity of 44.1 % in 51 MTC patients with increased Ct …”
supporting
confidence: 54%
See 2 more Smart Citations
“…They reported that sensitivity of 18 FDG PET-CT is 75% in patients with the calcitonin level above 1000 pg/ml and 20 to 36.8% when the calcitonin level is 500-1000 pg/ml or below 500 pg/ml. 18 FDG PET-CT has may be of value to evaluate response to applied therapy in cases with progressive disease but there is no diagnostic information for the individual somatostatin-receptor status if PRRT is considered [13].…”
Section: Discussionmentioning
confidence: 99%